2012
DOI: 10.1002/adsc.201100783
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Nickel(II) Chloride/Bis(tricyclohexylphosphine)nickel(II) Chloride‐Cocatalyzed Hydrodefluorination of Fluoroarenes and Trifluorotoluenes with Superhydride

Abstract: A simple and highly efficient approach for the hydrodefluorination of both fluoroarenes and trifluorotoluenes in the presence of lithium tri-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Some of these reactions are marred by the use of toxic and explosive reagents, production of stoichiometric metal waste, poor selectivity, and low functional‐group tolerance. Nevertheless, there has been an intense research interest in developing more efficient and reliable transition‐metal‐catalyzed hydrodehalogenation processes (mostly involving, Pd, Rh, Ru, Ni, and Fe) using Grignard reagents, alcohol and base,, hydrides,,, formic acid or its salt, hydrazine, and molecular hydrogen ,,,. Obviously, from an ecological perspective, the later reagent is considered to be the most efficient, clean, and atom‐economical reductant…”
Section: Methodsmentioning
confidence: 99%
“…Some of these reactions are marred by the use of toxic and explosive reagents, production of stoichiometric metal waste, poor selectivity, and low functional‐group tolerance. Nevertheless, there has been an intense research interest in developing more efficient and reliable transition‐metal‐catalyzed hydrodehalogenation processes (mostly involving, Pd, Rh, Ru, Ni, and Fe) using Grignard reagents, alcohol and base,, hydrides,,, formic acid or its salt, hydrazine, and molecular hydrogen ,,,. Obviously, from an ecological perspective, the later reagent is considered to be the most efficient, clean, and atom‐economical reductant…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, Cao et al illustrated a cocatalyst system composed of nickel(II) chloride, and bis(tricyclohexylphosphine)nickel(II)chloride was able to hydrodefluorinate various aryl fluorides in the presence of superhydride (Eq. 70) [124]. The hydrodefluorination of heterocycle-polyfluoroarenes has also been reported by Zhang et al in 2013.…”
Section: ð68; 69þmentioning
confidence: 64%
“…In continuation of the research on the hydrodefluorination reaction, Cao and coworkers reported various reaction conditions for different types of C-F bonds [24,[63][64][65]. They found that C-F bonds of fluoroarenes are more easily reduced with LiAl(O t Bu) 3 H than C-F bonds of α,α,α-trifluorotoluenes under the catalysis of NiCl 2 (PCy 3 ) 2 (Scheme 24d) [66].…”
Section: Page 25 Of 29mentioning
confidence: 95%